Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1465-9921-14-111
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary biomarkers in COPD exacerbations: a systematic review

Abstract: Exacerbations of COPD (ECOPD) represent a major burden for patients and health care systems. Innovative sampling techniques have led to the identification of several pulmonary biomarkers. Although some molecules are promising, their usefulness in clinical practice is not yet established. Medline and Highwire databases were used to identify studies evaluating pulmonary sampled biomarkers in ECOPD. We combined 3 terms for ECOPD, 3 for biomarkers and 6 for the sampling method. Seventy-nine studies were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 85 publications
2
51
1
2
Order By: Relevance
“…IL-8, myeloperoxidase, elastase) 4 were based on analysis of sputum or serum. Thus, our results represent the first biomarker that has been identified in vitro and, to our knowledge, M-CSF is the first to offer the possibility of discriminating between viral and bacterial causes of COPD exacerbations.…”
Section: Supplementary Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-8, myeloperoxidase, elastase) 4 were based on analysis of sputum or serum. Thus, our results represent the first biomarker that has been identified in vitro and, to our knowledge, M-CSF is the first to offer the possibility of discriminating between viral and bacterial causes of COPD exacerbations.…”
Section: Supplementary Discussionmentioning
confidence: 99%
“…While hospitalization and mortality due to these diseases are often the consequences of exacerbations triggered by pathogens 2, 3 , there is currently no way to study these processes in human lung outside of the clinical setting. Animal models of asthma and COPD exist; however, their clinical relevance is questionable because the anatomy, immune system and inflammatory responses exhibited by animal lungs differ greatly from those in humans [4][5][6] . For example, mucin-producing cells, which are central to the development of asthma, are less frequent in the respiratory tree of mice and rats compared with humans 6 .…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Numerous studies have shown that fibrinogen levels are elevated in stable COPD (even outside exacerbations) in relation to the increasing decline of FEV1 along with other biomarkers (CRP, white blood cells, TNF-α, IL-6, IL-8). 6,[10][11][12]24 Increased fibrinogen certifies systemic inflammation in stable COPD and may partially explain some systemic side effects such as muscle wasting, osteoporosis and cardiovascular effects. 5,6,30 The ECLIPSE study has demonstrated that an elevated fibrinogen in COPD is a predictive marker of an increased risk for exacerbations, hospitalization and mortality.…”
Section: Fibrinogenmentioning
confidence: 99%
“…6 The risk of having frequent exacerbations is clearly demonstrated by recognized studies in patients with specific criteria: previous exacerbation in the last year, decrease in FEV1s, increase in the score of St. George Questionnaire (life quality diminution), high levels of some inflammatory biomar-kers -neutrophils, C-reactive protein (CRP), fibrinogen, pro-calcitonin, eosinophils, IL-6, IL-8, chemokine ligand 18 (CCL-18/PARC), surfactant protein D (SP-D). [9][10][11] Simultaneously, elevated levels of CRP, fibrinogen and leukocyte count in COPD patients were associated with increased risk of having exacerbations. [12][13][14] In the same time, elevated levels of the three biomarkers are associated with an increased risk of major comorbidities in COPD.…”
mentioning
confidence: 99%
“…Thus, practically, exacerbations are difficult to diagnose and therefore it is a worthwhile task to explore potential biomarkers that can be appointed for clinical use [12] . Although some proteins have been suggested as potential markers of COPD exacerbation, up to now there is no single factor that can decisively identify it [13,14] .…”
Section: Introductionmentioning
confidence: 99%